Insuficiência cardíaca com fração de ejeção normal - Roscani, Meliza Goi [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (My University, 2010)
Heart failure with normal ejection fraction (HFNEF) is a complex syndrome that has been broadly studied since the last decade. It is caused by diastolic ventricular dysfunction demonstrated by complementary methods, such as hemodynamic study or echocardiogram, in the presence of a normal ejection fraction (EF). It affects primarily elderly individuals with comorbidities, such as systemic arterial hypertension, coronary failure and obesity. The physiopathological mechanisms are complex and multifactorial, involving the myocardial passive stiffness, the ventricular geometry, the pericardial restraint and the interaction between the ventricles. The main objectives of the treatment were to decrease the pulmonary venous congestion and the heart rate and control the comorbidities. There is no strong evidence that the use of specific medications, such as the angiotensin-converting enzyme inhibitors or beta-blockers can influence mortality. The poorer prognostic factors include advanced age, presence of kidney dysfunction, diabetes, functional class III and IV (NYHA) and advanced-stage diastolic dysfunction, with a restrictive pattern of ventricular filling. Another aspect that has been increasingly cited in the literature is the analysis of the role of the systolic function in HFNEF cases. All these aspects are analyzed in detail in the present review.
Heart failure with normal ejection fraction
Keywords: Cardiomegaly; Compliance; Diastole; Echocardiography; Heart failure